Chapter VI.1.4 The European Union and seabed mining - Singh, Pradeep A. (Taylor & Francis, 2024)
For years, exploration of seabed natural resources has been ongoing while exploitation in deep marine areas remained unrealistic due to land-based mineral availability and costs. However, mounting pressures from the green transition, climate change, and long-lasting fears of terrestrial minerals scarcity now bring exploitation prospects closer to reality. This is has caused concern to a growing chorus of States, scientists, industries, NGOs, and parts of civil society due to the potential environmental and social impacts of these activities. As a result, the idea of a moratorium or 'precautionary pause' is gaining ground. Yet, an important number of interpretation and implementation issues of the United Nations Convention on the Law of the Sea (UNCLOS) and the 1994 Agreement remain to be answered as a means to move forward in accordance with international law. This multidisciplinary book, designed to become the essential handbook on the matter, provides a global overview of the national, regional, and international regulatory frameworks applicable to the exploration and exploitation of seabed minerals on the continental shelf and the Area, as well as the related state of the science on the matter. By presenting historical and geopolitical context crucial to understanding regulation evolution, the book equips readers with foundational legal and policy knowledge. It furthermore addresses contemporary and prospective issues and offers unique insights into regional and national practices, including non-Party States to UNCLOS.